Micro-extrusion of ultrafine grained copper - Geißdörfer, Stefan; Rosochowski, A.; Olejnik, Lech; Engel, Ulf; Richert, Maria Mr (Proceedings of the 11th International Esaform Conference on Material Forming, 2008)
Because of the well known virtues of low cost and high productivity, metal forming technology is well suited for mass production of metal micro-components. However, scaling down metal forming processes proves to be problematic because, among other factors, the relatively coarse grain (CG) structure of micro-billets leads to non-uniform material flow and lack of repeatability during microforming. A substantial grain size reduction below one micron should help to prevent these problems. The aim of the presented study is to investigate a possibility of using an ultrafine grained (UFG) metal for micro-extrusion. The material used for this purpose is CP Cu often used for electrical applications. The UFG version of Cu is produced by severe plastic deformation at room temperature using up to 8 passes of equal channel angular pressing. The microstructure and compression properties of the UFG version of the material are tested. The microforming process of backward extrusion is carried out at room temperature using half cylindrical billets. The extrusion force, grain flow, shape representation and surface quality of the extruded micro-components are compared. © 2008 Springer/ESAFORM.
LFT Import::2019-08-05 (1530)
Keywords: ECAP; In-situ process observation; Micro-extrusion; Ultrafine grained metal